Information needs and barriers to patient-centered care in oncology: EtnobreastHER2, an ethnographic study with HER2+ MBC patients and their healthcare providers - García-Sáenz, José Ángel; Rodríguez-Lescure, Álvaro; Antolin, Silvia; Cantos, Blanca; Seguí, Miguel Ángel; Gimón, María Antonia; Rubio Renau, Raül; Solà Marsiñach, Carlota; Martín Illán, Jesús; Fonseca Vallejo, Rocío; Gimeno Guadalupe, Yaiza; Alfaro Oliver, Noelia; et al. (Frontiers in Medicine, 2025)
Introduction and objectivesQualitative evidence regarding the structural barriers embedded in healthcare ecosystems impacting Human Epidermal Growth Factor Receptor 2 metastatic breast cancer (HER2+ MBC) patients’ communication and information needs is scarce. This study explored patient and healthcare professionals’ perspectives on said structural barriers and communication delivery.MethodsEthnographic, qualitative, observational, multicenter and cross-sectional study with HER2+ MBC patients and Health Care Professionals. Qualitative data collected through remote semi-structured interviews with patients (n = 14) and healthcare professionals (n = 10). The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ)-C30 and the disease-specific EORTC QLQ-BR45 questionnaires were collected as Quality of Life measures.ResultsRegarding the communication and information needs of patients, there were four areas these were lacking most: (1) disease and treatment, (2) psychosexual support, (3) navigation of the healthcare and social security systems to reduce the financial burdens, and (4) patient associations. In reference to delivery of information from healthcare professionals, there were four areas that were lacking: (1) time, (2) interpersonal skills and communications training, (3) specialized oncology nursing training, and (4) lack of an evaluation system assessing patient-centered care and patient satisfaction.ConclusionResults emphasize how structural barriers embedded in healthcare systems can lead to and intensify information and communication gaps, which therefore emphasizes that to provide optimal, patient-centric care, these structural barriers must be addressed.